Huge Retroperitoneal Cyst Masquerading as Ovarian Tumour: A Case Report - Johan, Syamim; Hassan, Muhammad Firdaus; Hayati, Firdaus; Azizan, Nornazirah; Payus, Alvin Oliver; Edwin See, Un Hean (Frontiers in Surgery, 2020)
Retroperitoneal cystic mass is a rare surgical condition that is often misdiagnosed preoperatively. Here, we report a case of a 56-year-old woman who presented with abdominal swelling for a 1-year duration, which was associated with lower abdominal pain for 6 months. Her abdominal radiograph showed a huge radiopaque lesion, and contrast-enhanced computed tomography scan of the abdomen reported it as a left ovarian serous cystadenoma causing local mass effect to the left ureter leading to mild left hydronephrosis. She underwent exploratory laparotomy and noted there was a huge retroperitoneal cystic mass. The histopathological assessment finding was consistent with a benign retroperitoneal cyst. This case report aims to share the rare case of primary retroperitoneal lesions, which can cause a diagnostic challenge preoperatively to all clinicians despite advanced achievement in medical imaging.